Self-efficacy and self-regulation in football athletes: The moderating role of happiness - Shaleha, Aminatus; Jannah, Miftakhul (UIR Press, 2025)
Background: Self-regulation is a core psychological skill for football athletes because it enables them to maintain attention, manage emotions, and adjust behavior under competitive demands. Although self-efficacy is widely recognized as an important predictor of self-regulation, only a limited number of studies have examined whether positive affect, particularly happiness, moderates this relationship, leaving an empirical gap in understanding how cognitive and emotional resources interact in athlete functioning. Objective: This study aimed to investigate the influence of self-efficacy on self-regulation in football athletes and to test whether happiness moderates this association. Methods: A quantitative moderated regression design was used with 106 Indonesian male football athletes aged 14 to 22 years who were registered with professional or academy clubs. Data were collected using validated Indonesian versions of the Athlete Self-Efficacy Scale (ASES), the Self-Regulation Questionnaire (SRQ), and the short Oxford Happiness Questionnaire (OHQ). Measurement models demonstrated acceptable reliability and fit, and assumption checks indicated normal residuals, homoscedasticity, and no serious multicollinearity, supporting the use of Moderated Regression Analysis (MRA). Finding/Results: The findings showed that both self-efficacy and happiness significantly and positively predicted self-regulation, and happiness significantly moderated (attenuated) the relationship between self-efficacy and self-regulation. The final model explained over half of the variance in self-regulation. Conclusion: Although the cross-sectional, self-report, and entirely male sample limits causal interpretation and generalizability, the results highlight the importance of integrating confidence building strategies with happiness enhancing approaches in psychological skills training for football athletes. Future research is encouraged to examine additional moderators using longitudinal or experimental approaches.